Smart secondary polyurethane dispersions. Issue 12 (22nd March 2013) - Chen, Fei; Hehl, Judith; Su, Yu; Mattheis, Claudia; Greiner, Andreas; Agarwal, Seema
Abstract: Secondary dispersions of cationic segmented polyurethanes (PUs) with thermoresponsivity (upper critical solution temperature (UCST) in water), high solid contents and antibacterial properties are highlighted in this paper. PUs were prepared by polyaddition reactions and subsequent quaternization with methyl iodide. No additional stabilizers, organic solvents or special procedures were required to obtain stable aqueous dispersions containing up to 10 wt% PU; in contrast, stable dispersions were straightforwardly accessed by a combination of UCST behavior and repulsive electrostatic forces among the positively charged segments, which meets the requirements of a green chemistry process. Particle size and UCST strongly depended on the solid content of the dispersions and the content of poly(ethylene glycol) segments in the copolymers. The dispersions exhibited fast‐acting antibacterial properties against Escherichia coli . © 2013 Society of Chemical Industry Abstract : A straightforward method for the preparation of UCST PU dispersions with high solid contents without use of emulsifiers is highlighted. This is based on segmented cationic PUS with PEG block.